Ambiguous intimacy as queer potential: touch, desire and adolescence in She Monkeys. (August 2019) - Bradbury-Rance, Clara
This article analyses the ambiguous intimacies generated by the competition that permeates desire in Lisa Aschan's She Monkeys (2011). The article argues that in a new corpus of films about adolescence, the queerness of lesbian desire is evoked as a series of affects outside of figurative norms. Desire meets and is confused with other affects such as envy and disgust, all of which attach, sometimes simultaneously, to objects that do not always seem to recognise or permit them. Slow and languid scenes reveal desire's potential but rarely its achievement. The article explores the erotic potential of those intimacies that reside in the spaces between bodies, asking what happens to that potential when it is generated but immediately contained by the negotiations of control. In dialogue with psychoanalytic work on the ambivalent relations between desire, envy, attachment and idealisation, the article advances a reading of an affective mode of filmmaking that is saturated with desire but not defined by desire's labelling.